Efektivitas Pemberian Ikan Gabus Dengan Putih Telur Terhadap Penyembuhan Luka Perineum Pada Ibu Nifas Di Rumah Sakit Bakti Timah Sungailiat : Effectiveness of Giving Snakehead Fish with Egg White on Healing Perineal Wounds in Postpartum Mothers at Bakti Timah Hospital, Sungailiat - Sari, Indah Lugita (Indonesian Scholar Journal of Nursing and Midwifery Science (ISJNMS), 2025)
Introduction: Perineal wounds are injuries that occur during childbirth in the perineum. WHO found 2,7 million cases of perineal rupture in mothers in labor. In Asia, perineal rupture is 50% of the incidence of perineal rupture in the world. Based on data on the incidence of perineal rupture at RSBT Sungailiat in 2024. Data from January-May 2024 there were 18 people with grade 2 perineal rupture and 4 people. Methods: a case study research approach where a comparison was made of perineal wounds between two different treatment individu namely subjects who consumed snakehead fish and subjects who consumed egg white. The population in this study were post-partum mothers who came to the Hospital Bakti Timah Sungailiat in Bangka Regency. Results: The results of the study post-partum mothers with grade I perineal rupture were given snakehead fish and post-partum mothers with grade II perineal wounds were given egg white for 7 days and monitored 3 times. Discussion:  The results were obtained after giving 100 grams of snakehead fish per day for 7 days and monitoring the healing of perineal wounds using the REEDA scale and  The results were obtained after providing 6 egg whites per day for 7 days and monitoring the wound through REEDA scale. The mother consuming snakehead fish experienced longer healing compared to the post-partum mother with a grade 2 perineal rupture consuming egg whites.